Qardhul Hasan as a Green Financing Instrument for Environmentally Friendly MSMEs - Devira Al Azroh; Andriani Samsuri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The rapid development of the global economy can lead to the need for sustainable financing, especially in supporting environmentally friendly Micro, Small, and Medium Enterprises (MSMEs). This study analyzes the potential of qardhul hasan as a social financing instrument in supporting the development of environmentally friendly Micro, Small and Medium Enterprises (MSMEs) in Indonesia and explores the role of Islamic banking in the implementation of green financing. As an interest-free financing scheme, qardhul hasan offers an innovative solution for MSMEs that are constrained from accessing conventional financing due to high interest rates and strict requirements. In the context of green financing, qardhul hasan not only provides more inclusive access to capital but also encourages MSMEs to adopt sustainable business practices. These practices include the use of environmentally friendly technologies, ecological raw materials, as well as better waste management, which directly contribute to the achievement of the Sustainable Development Goals (SDGs), particularly related to climate action and inclusive economic growth. The research uses a qualitative method with a literature study approach to examine the relevance of qardhul hasan in supporting the sustainability agenda. The results show that qardhul hasan not only reduces the financial burden of MSMEs but also allows businesses to focus on developing their business, improving operational efficiency, and expanding markets. In addition, qardhul hasan strengthens the role of Islamic banking as a strategic actor in green financing by providing financial support for MSMEs that contribute to environmental conservation. With cross-sector synergy, qardhul hasan has great potential to become a key element in creating a balance between economic growth and environmental sustainability. This research is expected to provide academic and practical contributions in the development of sharia-based sustainable financing and strengthen Indonesia's commitment to climate change mitigation.